2021
DOI: 10.3390/cancers13061252
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Triggers Tamoxifen Resistance in Human Breast Cancer Cells by Preventing Drug-Induced Lysosomal Damage

Abstract: Endocrine resistance is a major complication during treatment of estrogen receptor-positive breast cancer. Although autophagy has recently gained increasing consideration among the causative factors, the link between autophagy and endocrine resistance remains elusive. Here, we investigate the autophagy-based mechanisms of tamoxifen resistance in MCF7 cells. Tamoxifen (Tam) triggers autophagy and affects the lysosomal compartment of MCF7 cells, such that activated autophagy supports disposal of tamoxifen-damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 66 publications
5
27
0
Order By: Relevance
“…Indeed, while 10 uM tamoxifen was able to transiently alkalinize the lysosome after 3 h treatment, measured by a reduction in lysotracker staining, ospemifene was not effective at a similar concentration (Fig EV5C). Also, we confirm previous data showing that the effect of tamoxifen on lysosomal alkalinization is reversible (Fig EV5C) (Actis et al , 2021).…”
Section: Resultssupporting
confidence: 93%
“…Indeed, while 10 uM tamoxifen was able to transiently alkalinize the lysosome after 3 h treatment, measured by a reduction in lysotracker staining, ospemifene was not effective at a similar concentration (Fig EV5C). Also, we confirm previous data showing that the effect of tamoxifen on lysosomal alkalinization is reversible (Fig EV5C) (Actis et al , 2021).…”
Section: Resultssupporting
confidence: 93%
“…MtnA also responds to genes and pathways of additional metabolic processes, autophagy, and apoptosis [ 229 ]. Overexpression of MT in cells can protect lysosomes from estrogen-induced damage and maintain viability while inhibiting autophagy [ 230 ]. Knockdown of metallothionein-3 inhibits late autophagy in irradiated glioma cells [ 231 ].…”
Section: Zinc and Autophagymentioning
confidence: 99%
“…In addition, a study utilizing RT-PCR to measure ATG5 levels in 60 breast cancer tissues found that trastuzumab-resistant patients had higher ATG5 levels than trastuzumab effective patients ( 92 ). Similarly, elevated autophagy markers in drug-resistant breast cancer cells have been reported for tamoxifen and fulvestran ( 93 , 94 ). In summary, it can be concluded that HIF-1α can lead to breast cancer resistance to endocrine drugs and cytotoxic drugs through upregulation of autophagy.…”
Section: Hif-1α Contributes To Drug Resistance In Breast Cancermentioning
confidence: 67%